Higher fat oxidation in running than cycling at the same exercise intensities - Capostagno, B.; Bosch, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2010)
This study examined the differences in fat and carbohydrate oxidation during running and cycling at the same relative exercise intensities, with intensity determined in a number of ways. Specifically, exercise intensity was expressed as a percentage of maximum workload (WLmax), maximum oxygen uptake (%VO2max), and maximum heart rate (%HRmax) and as rating of perceived exertion (RPE). Ten male triathletes performed maximal running and cycling trials and subsequently exercised at 60%, 65%, 70%, 75%, and 80% of their WLmax. VO2, HR, RPE, and plasma lactate concentrations were measured during all submaximal trials. Fat and carbohydrate oxidation were calculated from VO2 and VCO2 data. A 2-way ANOVA for repeated measures was used to determine any statistically significant differences between exercise modes. Fat oxidation was shown to be significantly higher in running than in cycling at the same relative intensities expressed as either %WLmax or %VO2max. Neither were there any significant differences in VO2max and HRmax between the 2 exercise modes, nor in submaximal VO2 or RPE between the exercise modes at the same %WLmax. However, heart rate and plasma lactate concentrations were significantly higher when cycling at 60% and 65% and 65-80%WLmax, respectively. In conclusion, fat oxidation is significantly higher during running than during cycling at the same relative intensity expressed as either %WLmax or %VO2max.